The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/fsn3.1967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oils prepared from the internal organs of the Japanese giant scallop (Patinopecten yessoensis) on cholesterol metabolism in obese type‐II diabetic KK‐Ay mice

Abstract: Cardiovascular diseases (CVD) are one of the leading causes of morbidity and mortality worldwide (World Health Organization, 2017). CVD are mostly caused by atherosclerosis which is formed in the fibrofatty lesions in the artery wall (Libby et al., 2019). The development of fibrofatty lesions requires high cholesterol and triacylglycerol (TAG) contents in the blood (Generoso et al., 2019; Libby et al., 2019). An improvement in dyslipidemia, including high TAG and cholesterol contents in blood, through medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…2 . Our previous study also showed that SCO intake increased liver Cyp7a1 expression level 11 . Hayashi et al reported that increasing taurinebinding βMCA TβMCA , an antagonist of FXR, in the ileum enhanced liver Cyp7a1 expression by suppressing the FXR/SHP1 pathway 47 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…2 . Our previous study also showed that SCO intake increased liver Cyp7a1 expression level 11 . Hayashi et al reported that increasing taurinebinding βMCA TβMCA , an antagonist of FXR, in the ileum enhanced liver Cyp7a1 expression by suppressing the FXR/SHP1 pathway 47 .…”
Section: Discussionmentioning
confidence: 76%
“…SCO contains higher EPA than standard TAG-type fish oil and includes phospholipids PL and TAG 8 . Our previous study showed that dietary SCO improved lipid metabolism and especially lowered cholesterol levels the serum and liver in obese type II diabetic KK-A y mice 11 . Until now, this effect of SCO has not been compared with other oils containing n-3 PUFA.…”
mentioning
confidence: 94%
“…Our previous study demonstrated that SCO intake decreased the serum and liver cholesterol content compared with n-3 PUFAcontaining oils, including tuna oil, menhaden oil, and krill oil (28,29). However, it is unclear whether the FA composition or PL of SCO is responsible for this cholesterol-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SCO contains approximately 20 wt% of PL and includes higher EPA than standard TG-type fish oil (26). Our previous study showed that SCO intake lowered the serum and liver cholesterol contents in mice (28), and this effect was not observed in krill oil and menhaden oil intake (29). However, it is unclear whether the FA composition or PL of SCO has a cholesterol-lowering effect.…”
Section: Introductionmentioning
confidence: 99%